Technological Spillovers and Determinants of Firm Productivity : Evidence from Vietnam’s Manufacturing Industry - Nguyen, Hai Minh (Indian Journal of Finance, 2022)
The paper aimed to study the determinants and spatial spillovers of enterprise productivity in the manufacturing industry in Vietnam during the period from 2010 – 2019. The spatial regression model was used to estimate the spatial dependence of enterprise-level TFP. The results showed that technology spillover occurred positively among firms in the region, and this effect decreased rapidly with spatial distance. Furthermore, the results also showed that firm productivity depended on firm characteristics and local market conditions. Further analysis showed that spillover effects’ strength was affected by many other factors: area, presence of FDI, administrative policies, border effect, infrastructure, weak financial factors, utility services, and human resources. These factors created favorable conditions for the smooth connection between major economic centers, creating strong inter-regional spillover effects. From the findings, the study proposed important policy implications.